Variation in Soil Properties along a Catena in kwambai Taraba State, Nigeria - R, Mbashak.; A.Y, Garjila; PK, Gideon; N Y, Yakubu; M.L, Rikin (International Journal of Environment, Agriculture and Biotechnology, 2019)
The study was carried out to determine the variation in soil properties within units and along a catena, significant of variation to soil mapping and soil management at kwambai, Takum, within latitude 7o5 N and longitude 9o5 D E to 10o 10oE .Taraba State. Soil sample were collected from upland, slope and lowland areas of the catena at the depth of 0-15cm and 15-30cm at 3 composite,18 samples were collected. Soil properties analyzed include pH, Total Acidity EC(dS/m), Ca(Meg/Kg), Mg(Meg/Kg, K(Meg/Kg), Na(Meg/Kg), Base saturation%, TEB(Meg/Kg) ECEC(Meg/Kg), P(ppm), N%,O.C%,C:N ratio. Sand has the highest fraction in the soil. The soil is predominantly sandy clay loam. Clay loam in lowland surface, loam and sandy clay are less according to textural class. Grayish brown dominate the soil, dull brown in upland subsurface, others are brown, orange,and brownish grey.In upland area EC, Ca, Mg ,TEB, N and OC decrease with depth while others increase with depth. In slope area Total acidity, Ca, Mg, TEB, ECEC and P Increase with depth while others decrease with depth. In Lowland area Ca, Mg, Na, TEB, Base saturation, ECEC, and N Increase while others decrease with depth There is Significance differences in soil properties down the catena. There is no change in EC. C:N ratio has the highest coefficient of variation of 40.8% while base saturation has the lowest with 1.2% in surface down the catena, the highest in subsurface is total acidity with 55.5% and the lowest is C:N ratio with 1.0%. The following recommendations were made. More samples to be collected during Mapping, the area interval should be reduced. Management can be easily be done in the soil. Application of lime to correct soil acidity should be moderate; fertilizer application should be not be uniform because of variation in the Landscape area.